Elements of cultural scripts of trauma sequelae among trauma victims in East Africa - Mutuyimana, Celestin; Maercker, Andreas (Frontiers in Psychology, 2023)
Background As a new, unifying approach to mapping the cultural expressions of trauma sequelae, cultural scripts of trauma sequelae are empirically investigated here for the first time in a primarily qualitative study. Elements of Cultural Scripts of Trauma (CST) include the typical symptoms and appraisals of changes of those who have experienced traumatic events. These elements refer to the value orientations in the given culture. Aims To identify post-traumatic cultural scripts’ elements and their groupings, as expressed by trauma survivors from the East African population, and to explore the cultural values that serve as a reference to such scripts’ elements. Methods Semi-structured, in-depth interviews were conducted in nine focus groups of trauma survivors and trauma experts. Grounded theory was the basis for the content analysis, and MAXQDA was used for coding and grouping. Semi-quantitative analyses of the frequency of groupings followed. Results The study extracted 270 elements of the cultural scripts of trauma. Three stages of cultural scripts’ elements were identified including unspeakable, heart wounds and painful scars and growth. The reported elements are only those in the three last stages and they are grouped into six categories, such as cognitive appraisals, worldview, interpersonal relationships, body-related, positive changes and changes in family interest and management, while the elements of the first stages are not codable as the survivors do not yet get the words of their expressions. The cultural values that served as a reference consisted of holding the sadness, Christianity, community reputation, solidarity, social connectedness, social cynicism, and reproductiveness, among others. Discussion This comprehensive study with participants from several countries in East Africa collected a large number of elements of cultural scripts of trauma for this regional area. Notably, these elements were based mostly on man-made traumas, such as the genocide against the Tutsis in Rwanda. Further steps in the CST investigation are subject to future studies, such as a more systematic investigation of the relationship with cultural values and the temporal relationships within the scripts.